2015
DOI: 10.1016/j.ijid.2015.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the immunizing effect of the rubella epidemic in Japan, 2012-14

Abstract: Susceptible pockets remain in Japan, exposing the country to risk of additional rubella epidemics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…The epidemic in Japan has indicated that a major rubella epidemic can occur with adult patients making up the majority of cases. Given the limited immunising effect of the 2012–2014 epidemic, 24 our findings call for a supplementary vaccination among those remaining susceptible.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…The epidemic in Japan has indicated that a major rubella epidemic can occur with adult patients making up the majority of cases. Given the limited immunising effect of the 2012–2014 epidemic, 24 our findings call for a supplementary vaccination among those remaining susceptible.…”
Section: Discussionmentioning
confidence: 77%
“…The unfortunate tragedy that was identified in Greece in the 1990s 9 has been repeatedly experienced by present day Japan. While a recently published study focused on estimating the impact on the age-specific rubella seroprevalence of the most recent epidemic in Japan from 2012 to 2014, 24 the present study has comprehensively assessed the herd immunity in Japan through the analysis of longitudinal seroepidemiological data, which allowed us to compare between the age-standardised seropositive proportion and the theoretical herd immunity threshold, and, moreover, an elevated age at infection over time was confirmed based on an analysis of reported case data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spatial heterogeneity in susceptibility could act as the key to discriminating the metapopulation model from homogeneous models, and our approach was unable to capture that aspect. It should be remembered that the susceptible pocket was observed mainly among males aged 35–49 years in Japan [ 19 , 20 ], which we intend to address in the forthcoming study with age structured model. The fraction of this “high risk” subpopulation may vary by prefecture and heterogeneous contact patterns would also differ.…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, the country remains prone to imported cases and experienced a rubella epidemic during 2012-14 (Mori et al, 2017). Moreover, owing to the absence of an identifiable increase in the proportion of rubella antibody-positive individuals following the 2012-14 epidemic (Nishiura et al, 2015), another epidemic began in August 2018. Because the remaining susceptible people are adult male, and owing to the elevated age at infection over time, cases during both the 2012-14 epidemic and the ongoing 2018 epidemic are most frequently seen in adults National Institute of Infectious Diseases, 2018).…”
Section: Introductionmentioning
confidence: 99%